Optimalisasi Pemanfaatan Limbah Bonggol Jagung Menjadi Briket Di Desa Purbo Untuk Meningkatkan Nilai Produksi Dan Ekonomi Kreatif - Anggraeni Kusumaningrum; Kirana Primandini; Kurnianda Puspa Widyaningrum (Jurnal Bina Desa, 2026)
Corncob waste is one of the agricultural wastes that has not been widely utilized in Purbo Village, despite its potential to be processed into an economically valuable alternative energy source, such as briquettes. This community service aims to optimize the utilization of corncob waste through briquette production, with the hope of increasing economic value and fostering creative economy in the village. The methods used include technical training for the local community on the briquette production process, starting from the collection of corncobs, drying, to the carbonization and briquette molding process. The results of this activity show an increase in the skills and knowledge of the community in processing waste into high-value products. In addition, the production of corncob briquettes successfully provided an additional source of income for the people of Purbo Village. Thus, this activity not only reduces agricultural waste but also contributes to the improvement of the economic welfare of the village community.